2011
DOI: 10.1111/j.1439-0507.2010.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for pathogenic fungi

Abstract: Photodynamic therapy (PDT) is a minimally invasive approach, in which a photosensitiser compound is activated by exposure to visible light. The activation of the sensitiser drug results in several chemical reactions, such as the production of oxygen reactive species and other reactive molecules, whose presence in the biological site leads to the damage of target cells. Although PDT has been primarily developed to combat cancerous lesions, this therapy can be employed for the treatment of several conditions, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 49 publications
(101 reference statements)
0
50
0
2
Order By: Relevance
“…Several studies that evaluated azole-resistant Candida species, noted that these strains were sensitive to PDT [11][12][19][20] . The photosensitizer and light application specifically on the site affected by candidiasis, dramatically reduces the local and systemic side effects, allowing the photodynamic therapy to be seen as a promising treatment against Candida albicans 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies that evaluated azole-resistant Candida species, noted that these strains were sensitive to PDT [11][12][19][20] . The photosensitizer and light application specifically on the site affected by candidiasis, dramatically reduces the local and systemic side effects, allowing the photodynamic therapy to be seen as a promising treatment against Candida albicans 21 .…”
Section: Discussionmentioning
confidence: 99%
“…It is used with different purposes in microbiology and pharmacology for quite some time and, lately, has been applied on PDT as a photosensitizing drug in association with a continuous light source. So that the photosensitizer can be one light-activated by laser, the light applied must present a specific wavelength 6,20 . In this study, the red light with a wavelength of 660 nm was used, corresponding to the absorption spectrum of methylene blue, and was adjusted to the appliance before illumination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target cells must be first exposed to PS for a specific period of time, known as pre-irradiation time (PIT), before illumination. PDT results in reactive oxygen species (ROS), which promote cell damage and death [9][10][11]. The development of microbial resistance to such therapy seems to be improbable, since the mechanism of action involves multiple targets and ROS are non-specific agents.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous published studies have shown PDT to be highly effective in the in vitro inactivation of fungi (19,20,31). In addition, it is considered that the development of resistance to PDT by microbes is an unlikely event, because PDT is typically a multitarget process, which is a difference between PDT and most other antifungal drugs (22).…”
mentioning
confidence: 99%